Immobilization of Lipase A from Candida antarctica onto Chitosan-Coated Magnetic Nanoparticles - Rodolpho R. C. Monteiro; Paula J. M. Lima; Bruna B. Pinheiro; Tiago M. Freire; Lillian M. U. Dutra; Pierre B. A. Fechine; Luciana R. B. Gonçalves; Maria C. M. de Souza; José C. S. dos Santos; Roberto Fernandez-Lafuente (International Journal of Molecular Sciences, 2019)
In this communication, lipase A from Candida antarctica (CALA) was immobilized by covalent bonding on magnetic nanoparticles coated with chitosan and activated with glutaraldehyde, labelled CALA-MNP, (immobilization parameters: 84.1% ± 1.0 for immobilization yield and 208.0 ± 3.0 U/g ± 1.1 for derivative activity). CALA-MNP biocatalyst was characterized by X-ray Powder Diffraction (XRPD), Fourier Transform Infrared (FTIR) spectroscopy, Thermogravimetry (TG) and Scanning Electron Microscope (SEM), proving the incorporation of magnetite and the immobilization of CALA in the chitosan matrix. Besides, the immobilized biocatalyst showed a half-life 8–11 times higher than that of the soluble enzyme at pH 5–9. CALA showed the highest activity at pH 7, while CALA-MNP presented the highest activity at pH 10. The immobilized enzyme was more active than the free enzyme at all studied pH values, except pH 7.